A tent pitching scheme motivated by Friedrichs theory. (September 2015) - Gopalakrishnan, Jay; Monk, Peter; Sepúlveda, Paulina
Abstract Certain Friedrichs systems can be posed on Hilbert spaces normed with a graph norm. Functions in such spaces arising from advective problems are found to have traces with a weak continuity property at points where the inflow and outflow boundaries meet. Motivated by this continuity property, an explicit space–time finite element scheme of the tent pitching type, with spaces that conform to the continuity property, is designed. Numerical results for a model one-dimensional wave propagation problem are presented.